Multibeam bathymetry raw data (Atlas Hydrosweep DS 2 echo sounder entire dataset) of RV METEOR during cruise M58/1 - Andrew Akwasi Antobreh; Andrea Gerriets; Britta Knefelkamp; Sebastian Krastel; Franziska Richter; Lars Zühlsdorff; Horst D Schulz (PANGAEA, 2025)
Raw bathymetry data were collected using the ship extquotesingles own Atlas Hydrosweep DS2 multibeam echosounder during the RV METEOR cruise M58/1. The cruise took place on the Northwest Africa continental margin between 2003-04-15 and 2003-05-12 (Dakar, Senegal - Las Palmas, Spain). Bathymetry data were recorded together with sub-bottom (Parasound) profiling along all seismic profiles and transits between stations. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. No ancillary sound velocity profiles (SVP) data from the cruise are archived at the BSH, thus no SVP files are added to this dataset. Data are unprocessed and therefore can contain incorrect depth measurements (artifacts). Data can be processed e.g. with the open source software package MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, http://www.mbari.org/products/research-software/mb-system/, 2022).